Analisis Pengaruh Foreign Direct Invesment, Upah, dan Ekspor terhadap Penyerapan Tenaga Kerja di Industri Manufaktur di Indonesia - Tirta Candra Winata; I Nyoman Wahyu Widiana (Lembaga Pengembangan Kinerja Dosen, 2026)
The manufacturing industry is a strategic sector that plays a vital role in Indonesia’s economy, serving as a major contributor to the Gross Domestic Product (GDP) and the largest absorber of formal labor. Over the past three decades, this sector has faced various global dynamics, including technological advancements, automation, and fluctuations in investment and exports, all of which influence labor structures. Amid the transition toward Industry 4.0, it is essential to understand how macroeconomic factors such as Foreign Direct Investment (FDI), wages, and exports shape employment absorption in the manufacturing sector. This study analyzes the effects of these variables on Indonesia’s manufacturing employment from 1994 to 2024 using a quantitative approach with secondary data from the Central Bureau of Statistics (BPS) and the Investment Coordinating Board (BKPM). Multiple linear regression analysis using EViews was employed to examine both simultaneous and partial effects. The findings show that FDI, wages, and exports significantly influence employment absorption simultaneously. Partially, FDI has a positive but insignificant effect, indicating the dominance of capital-intensive foreign investment. Conversely, wages and exports have positive and significant effects. These results highlight that productivity-aligned wage increases and strong export performance can expand production capacity and generate new jobs. Therefore, optimizing labor-intensive investment, implementing proportional wage policies, and strengthening export performance are crucial strategies to enhance employment absorption in Indonesia’s manufacturing sector.